2018
DOI: 10.12968/coan.2018.23.6.322
|View full text |Cite
|
Sign up to set email alerts
|

Sacroiliac luxation in small animals: treatment options

Abstract: The term sacroiliac luxation-fracture (SIL/F) denotes traumatic separation of the ilial wing from the sacrum. This injury typically results from a traumatic event (most commonly a road traffic accident) and consequently is often seen with concomitant pelvic and/or other orthopaedic injuries. When indicated, the method of choice for SIL/F repair is lag screw fixation, which can be achieved via open reduction and internal fixation or minimally invasive osteosynthesis. The prognosis is in part affected by proper … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 20 publications
1
6
0
Order By: Relevance
“…Fauron and Déjardin stated that SIL in older animals are usually accompanied by orthopedic damage [9]. In direct proportion to this, in the present study, 53.8% of the cases over the age of 1 had at least one injury accompanying SIL, and ST was decided in 39.5% of these cases and CT in 60.5%.…”
Section: Figure 1 Graphical Representation Of the Relationships Betwe...supporting
confidence: 61%
See 3 more Smart Citations
“…Fauron and Déjardin stated that SIL in older animals are usually accompanied by orthopedic damage [9]. In direct proportion to this, in the present study, 53.8% of the cases over the age of 1 had at least one injury accompanying SIL, and ST was decided in 39.5% of these cases and CT in 60.5%.…”
Section: Figure 1 Graphical Representation Of the Relationships Betwe...supporting
confidence: 61%
“…In addition, there are some authors who support this view [7,13,[21][22][23]. Raffan et al reported that neurological damage developed in almost half of the cases with SIL, which they included in their study, and they stated that neurological damage became permanent in some of the cases with neurological damage [9]. Some authors emphasized that apart from TI , screws coming out of the sacrum, especially in cases of ST carry the risk of iatrogenic damage to the cauda equina dorsally, lumbosacral intervertebral disc cranially, lumbosacral plexus ventrally, and sacral vessels medially [6,17,[21][22].…”
Section: Figure 1 Graphical Representation Of the Relationships Betwe...mentioning
confidence: 95%
See 2 more Smart Citations
“…Moreover, some investigators reported a good to excellent outcome with femoral head-and-neck excision and a generally favorable prognosis for conservative management of pelvic fractures [ 2 , 6 - 8 , 29 , 32 - 34 ]. Reportedly, 64-75% of dogs and 82.35% of cats presenting with pelvic fractures had good to excellent outcomes with conservative treatment [ 8 , 14 ] when the candidates for this treatment were chosen [ 16 , 17 ]. Although pelvic fractures were historically managed conservatively in cats [ 3 , 11 ].…”
Section: Discussionmentioning
confidence: 99%